2018
DOI: 10.1021/acs.jced.7b00768
|View full text |Cite
|
Sign up to set email alerts
|

The Solid–Liquid Equilibrium and Crystal Habit of l-Carnitine Fumarate

Abstract: The solid–liquid equilibrium data of l-carnitine fumarate in methanol + (ethanol/1-propanol/2-propanol) binary mixed systems were determined at temperatures ranging from 288.15 to 328.15 K, while the solubility data of l-carnitine fumarate in (methanol +1-butanol) mixtures were determined from T = (293.15 to 333.15) K because of its low solubility in low temperature. All experimental data were obtained by the gravimetric method under atmospheric pressure. At each composition point, the data increases with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Liu and co-workers synthesized well-defined hierarchical radial Ni x P nanospheres on Ni foam by a facile one-step co-electrodeposition method for HER. [60] Ni x P electrocatalyst achieved a current density of 10 mA cm -2 , low Tafel slope of 55 mV dec -1 in 1 m KOH at only 63 mV overpotential.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Liu and co-workers synthesized well-defined hierarchical radial Ni x P nanospheres on Ni foam by a facile one-step co-electrodeposition method for HER. [60] Ni x P electrocatalyst achieved a current density of 10 mA cm -2 , low Tafel slope of 55 mV dec -1 in 1 m KOH at only 63 mV overpotential.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…By changing the composition of the electrolyte and simple technique craft adjustment, electrodeposition has the ability to get the optimized compounds with desired nano-architecture and composition, which cater to the trend of simple strategies to develop new nanofunctional materials. Of note, amorphous compounds can be easily synthesized through electrodeposition, and full characterization analysis confirms the enrichment defects that result in the increasing active sites as well as unique electronic structures, resulting in a qualitative improvement in the catalytic performance of materials [61,62]. In addition to synthesize catalysts by one-step electrodeposition, many studies involve the synthesis or modification of precursors by electrodeposition.…”
Section: Introductionmentioning
confidence: 94%
“…On the premise that no impurity atoms are introduced, both acid and alkali are used to pre-adjust to the specified pH condition, and buffer solvent are added to stabilize the pH change, like H 3 BO 3 . Last but not the least, length of time for electrodeposition determines the thickness of coating or the size of the nanostructure, and only a moderate amount can expose the most active sites for better catalysis activity [62,73,112].…”
Section: Electrolyte Additive and Multiple Regulatory Factorsmentioning
confidence: 99%
“…In recent years, transition metal‐based catalysts with rich earth elements have attracted widespread attention as alternative materials for noble metal catalysts, such as transition metal oxides, [6–7] nitrides, [8–9] sulfides, [10–11] and phosphides [12–13] . Among the abovementioned nonnoble metal catalysts, transition metal phosphides (TMPs) have been widely used in hydrogen production due to their rich active sites and good conductivity [14–18] . Recent studies have shown that bimetallic phosphides can provide higher catalytic activity owing to their synergistic effect [19–20] .…”
Section: Introductionmentioning
confidence: 99%